A numerical and experimental study of RF shimming in the presence of hip prostheses using adaptive SAR at 3 T. Issue 6 (25th February 2019) - Destruel, Aurelien; Fuentes, Miguel; Weber, Ewald; O'Brien, Kieran; Jin, Jin; Liu, Feng; Barth, Markus; Crozier, Stuart
Abstract : Purpose: Parallel transmission techniques in MRI have the potential to improve the image quality near metal implants at 3 T. However, current testing of implants only evaluates the risk of radiofrequency (RF) heating in phantoms in circularly polarized mode. We investigate the influence of changing the transmission settings in a 2‐channel body coil on the peak temperature near 2 CoCrMo hip prostheses, using adaptive specific absorption rate (SAR) as an estimate of RF heating. Methods: Adaptive SAR is a SAR averaging method that is optimized to correlate with thermal simulations and limit the temperature to 39°C near hip implants. The simulated peak temperature was compared when using whole‐body SAR, SAR10g, and adaptive SAR as a constraint for the maximum allowed input power. Adaptive SAR was used as a fast estimate of temperature to evaluate the trade‐off between good image quality and low heating near the hip implants. Electromagnetic simulations were validated by simulating and measuring B1 maps and electric fields in a phantom at 3 T. Results: Simulations and measurements showed excellent agreement. Limiting whole‐body SAR to 2 W/kg and SAR10g to 10 W/kg resulted in temperatures up to 49.3°C and 40.7°C near the hip implants after 30 minutes of RF exposure, respectively. Predictions based on adaptive SAR limited the temperature to 39°C, and allowed to improve the B1 field distribution while preventing peak temperatures near the hip implants. Conclusion: Significant RF heating can occur at 3 T near hip implants when parallel transmission is used. Adaptive SAR can be integrated in RF shimming algorithms to improve the uniformity and reduce heating.